2007
DOI: 10.1504/ijmed.2007.011791
|View full text |Cite
|
Sign up to set email alerts
|

Entrepreneurial skills assessment: an exploratory study

Abstract: Research Interests include entrepreneurship, legal and management issues in small and medium-sized businesses and virtual corporations. Doug Eichholz, Graduate Research Assistant, School of Business, Emporia State University. Research interests include entrepreneurship, ethics, and management issues in small and medium-sized businesses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
51
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(54 citation statements)
references
References 27 publications
(21 reference statements)
0
51
0
Order By: Relevance
“…The lack in technical skills that can be complemented by the ability and willingness to learn; the lack of creative problemsolving skills that can be complemented by following instructions by superiors. Relating these observations back to the categories of skills necessary for entrepreneur proposed by William et al (2007), the technical skills (belonging to the technical skills category) are complementary to the learning skills (personal maturity and managerial skills category); creative problem-solving skills (personal maturity, technical and entrepreneurial skills category) complements the ability to follow instructions (personal maturity and managerial skills category).…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…The lack in technical skills that can be complemented by the ability and willingness to learn; the lack of creative problemsolving skills that can be complemented by following instructions by superiors. Relating these observations back to the categories of skills necessary for entrepreneur proposed by William et al (2007), the technical skills (belonging to the technical skills category) are complementary to the learning skills (personal maturity and managerial skills category); creative problem-solving skills (personal maturity, technical and entrepreneurial skills category) complements the ability to follow instructions (personal maturity and managerial skills category).…”
Section: Discussionmentioning
confidence: 90%
“…The questions are as below. Referring to Table 1, the skills are grouped into categories based on William's suggestion (William et al, 2007), as indicated by the skills in the brackets. The questions with their corresponding evaluation factors are listed in the table.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The basic theoretical and empirical knowledge on enterprise performance, entrepreneurship, and market dynamics of entry and exit of enterprises are based on studies for western market economies, for transition and emerging market economies (Antončič et al, 2002;Hudson, 1986;Dunne et al, 1988;Davelaar, 1991;Machin and Reenen, 1993;Storey, 1994;Geroski and Walters, 1997;Audretsch et al, 2006;Smith et al, 2007;Kraus and Schwarz, 2007;Bojnec and Xavier, 2004. We aim to investigate the changes in the number and importance of large wood industry enterprises on the dynamics of entry of newly established small enterprises as a response to the emerging gaps in supply of products and services, which have occurred with the exit of large enterprises or with the changing their size.…”
Section: Dynamics Of Large Enterprises As Determinant Of Dynamics Of mentioning
confidence: 99%
“…In the first part, we present theoretical background as a starting point for empirical analysis of the dynamics of the wood industry enterprises in Slovenia. The research is based on economic theory and empirical analysis on performances of enterprises and determinants, which are determining entry and exit of enterprises (Antončič et al, 2002;Antončič, 2007;Hudson, 1986;Dunne et al, 1988;Davelaar, 1991;Machin and Reenen, 1993;Storey, 1994;Geroski and Walters, 1997;Audretsch et al, 2006;Smith et al, 2007;Kraus and Schwarz, 2007;Bojnec and Xavier, 2004. In the second, empirical part of this paper, we present empirical results of the research of the sample of micro and small Slovenian enterprises, which operate in the wood industry in Slovenia.…”
Section: Introductionmentioning
confidence: 99%